2005
DOI: 10.1111/j.0272-4332.2005.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of True Salmonella Prevalence Jointly in Cattle Herd and Animal Populations Using Bayesian Hierarchical Modeling

Abstract: The Finnish salmonella control program (FSCP) for beef production is based on both randomized and selective testing of herds and animals. Sampling of individual animals in abattoirs is randomized. Herds are selectively tested for salmonella on the basis of clinical symptoms and/or other factors. Risk assessment of FSCP is inherently difficult due to the complexity of the complete data set, especially if the detailed labeling of the testing types is lost. However, for a risk assessment of the whole production c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…A similar Salmonella prevalence in feedlot cattle had been reported before and been attributed to low hygiene in feedlots (Vanselow et al 2007;Khaitsa et al 2007a). Also, previous reports of Salmonella prevalence in range cattle (Ranta et al 2005) and dairy cattle (Sorensen et al 2003;Huston et al 2002) have been comparable to what is reported by this study, and have been consistently lower than in feedlot cattle. However, the isolation of Salmonella in sick or dead cattle (13.6%) and sick humans (41.2%) was indicative of its increasing role in causing disease in both groups of hosts (Besser et al 2000;Padungtod and Kaneene 2006).…”
Section: Salmonella From Clinical Cases Of Animals and Humanssupporting
confidence: 90%
“…A similar Salmonella prevalence in feedlot cattle had been reported before and been attributed to low hygiene in feedlots (Vanselow et al 2007;Khaitsa et al 2007a). Also, previous reports of Salmonella prevalence in range cattle (Ranta et al 2005) and dairy cattle (Sorensen et al 2003;Huston et al 2002) have been comparable to what is reported by this study, and have been consistently lower than in feedlot cattle. However, the isolation of Salmonella in sick or dead cattle (13.6%) and sick humans (41.2%) was indicative of its increasing role in causing disease in both groups of hosts (Besser et al 2000;Padungtod and Kaneene 2006).…”
Section: Salmonella From Clinical Cases Of Animals and Humanssupporting
confidence: 90%
“…For surveillance systems where systematically collected data are available, the BBN formulation is a bridge to a fully Bayesian analysis using Markov chain Monte Carlo methods to obtain posterior estimates of prevalence based on prior distributions of model parameters. ( 22–24 ) The dependence on prior distributions makes such methods inherently controversial ( 25 ) but the scenario tree and BBN approaches have a similar credibility problem when there is uncertainty in detection probabilities and other parameters. In both approaches, many sources of uncertainty—e.g., in parameter values, bounds, and model structure—are ignored for the sake of exposition and mathematical tractability.…”
Section: Discussionmentioning
confidence: 99%
“…Bayesian inference is increasingly used in many research disciplines, including veterinary epidemiology (Dohoo et al, 2009). A few examples in this field are applications for diagnostic test evaluation, disease mapping, and risk assessment (e.g., Toft et al, 2005;Best et al, 2005;Ranta et al, 2005). The growing popularity of Bayesian analysis is often motivated by its advantage in handling complicated empirical problems which are difficult within the classical frequentist approach (Dohoo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%